Policy mix and debt sustainability : evidence from fiscal policy rules - Peter Claeys (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper characterises rules-based fiscal policy setting. Basically, we translate a standard monetary policy rule into a simple fiscal policy rule. We then infer on fiscal policymakers' reaction coefficients by testing the rule with GMM. Interaction is also tested directly by the inclusion of monetary policy setting. Our results qualify existing evidence on systematic fiscal policy in two respects. First, fiscal policy usually stabilises public debt. And there is indeed substantial interaction between fiscal and monetary policy via the debt channel. Second, sustainability is achieved with a 'stop-go? cycle of consolidation. Consolidation does not come at the cost of less cyclical stabilisation unless debt ratios are high.
Keywords: E63; E61; 330; monetary policy; fiscal policy; policy interaction and policy rules; debt sustainability; Finanzpolitik; Geldpolitik; Regelgebundene Politik; Transmissionsmechanismus; Öffentliche Schulden; EU-Staaten; Japan; Vereinigte Staaten